Arthroscopic anterior cruciate ligament reconstruction with central quadriceps tendon bone (CQTB) graft: An outcome study in fifty Indian patients - Sharma, Saurabh; Joshi, Gururaj; Philip, Vivek M.; Kaushal, Nitin (International Journal of Research in Medical Sciences, 2017)
Background: Arthroscopic ACL reconstruction using biologic autografts is the current gold standard in the management of symptomatic ACL tears. The commonly used BPTB (Bone-Patellar Tendon-Bone) and quadrupled hamstring tendon grafts have their own disadvantages. This study was conducted to evaluate the efficacy of CQTB (Central Quadriceps Tendon Bearing) graft as an autograft for ACL reconstruction in relieving instability in ACL deficient knees. Methods: 50 patients (45males; 5 females) with symptomatic ACL laxity, who underwent arthroscopic ACL reconstruction using the CQTB graft were followed up for 1 year. The functional improvement was analyzed by comparing the pre-operative Lysholm scores with those at 03 months, 06 months and 12 months post operatively. The objective improvement was analyzed comparing the Anterior Drawer and Lachman test grades pre-operatively and after 1 year follow up. The mean length of the graft and the post-operative morbidity were also noted. Results: The average Lysholm scores improved from a pre-operative value of 44.34 to 78.98,87.86 and 91.58 at 03months,06 months and 1 year respectively. (p<0.05; ANOVA). The number of patients with Grade I, II and III laxities on Anterior Drawer test improved from 01, 36 and 12 respectively to 43, 06 and 01 respectively 1 year after surgery (p<0.05; paired t test). The number of patients with Grade I, II and III laxities on Lachman test reduced from 1, 34 and 15 y to 39, 10 and 01 respectively. The average thickness of graft harvested was 9.21mm. Conclusions: CQTB autograft is a viable option along with other available autografts in its ability to reconstruct native ACL, without any hazards and additional complications.